1994
DOI: 10.1002/bjs.1800810629
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy prolongs survival in inoperable pancreatic carcinoma

Abstract: Forty-three patients with irresectable advanced pancreatic cancer were randomized to receive chemotherapy using a combination of 5-fluorouracil, Adriamycin and mitomycin or no chemotherapy. Groups were well matched with regard to age, extent of disease and performance status on entry. Chemotherapy was well tolerated and, although common, side-effects were usually mild. Psychological measurements based on the Hospital Anxiety and Depression score were made in 31 patients. These showed significantly less depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
81
1
13

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(96 citation statements)
references
References 13 publications
1
81
1
13
Order By: Relevance
“…Most of the incorporated EPA appears to remain in the phospholipid component of cell membranes (Brown and Subbaiah, 1994), although the cytoplasmic lipid accumulation observed in the present study may suggest that other mechanisms are also important. However, it has been shown that the relative quantity of polyunsaturated fatty acids in the cell membrane may play an important role in regulation of proliferation and cellular functions (Brown and Subbaiah, 1994;Pan et al, 1990;Bandyophadhyay et al, 1993). It is possible that EPA may alter the microenvironment of surface receptors or signalling proteins in the cell membrane, thereby inducing inappropriate signalling moieties and initiating cell cycle arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the incorporated EPA appears to remain in the phospholipid component of cell membranes (Brown and Subbaiah, 1994), although the cytoplasmic lipid accumulation observed in the present study may suggest that other mechanisms are also important. However, it has been shown that the relative quantity of polyunsaturated fatty acids in the cell membrane may play an important role in regulation of proliferation and cellular functions (Brown and Subbaiah, 1994;Pan et al, 1990;Bandyophadhyay et al, 1993). It is possible that EPA may alter the microenvironment of surface receptors or signalling proteins in the cell membrane, thereby inducing inappropriate signalling moieties and initiating cell cycle arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, surgical resection is rarely feasible, since most patients present with advanced inoperable disease. Although some groups have demonstrated slightly improved survival with conventional cytotoxic chemotherapy (Palmer et al, 1994), there is, at present, no effective treatment for advanced pancreatic cancer. There is, therefore, a need to develop selective and relatively non-toxic treatment regimens directed at reducing the morbidity and mortality associated with pancreatic cancer.…”
mentioning
confidence: 99%
“…Several studies have reported encouraging results with single chemotherapy agents or combination treatments (Mallinson et al, 1980;Casper et al, 1994;Palmer et al, 1994;Carmichael et al, 1995;Burris et al, 1997) and gemcitabine has been compared to 5-fluorouracil (5-FU) in a phase III study in patients with advanced pancreatic cancer (Burris et al, 1997). The results of this study suggested that patients receiving gemcitabine had both an improved survival and patient benefit compared to those patients receiving 5-FU and these data and data from several other studies have led to the widespread acceptance of gemcitabine as first-line therapy in patients with advanced pancreatic cancer Carmichael et al, 1995;Rothenberg et al, 1996;Burris et al, 1997;Storniolo et al, 1999).…”
mentioning
confidence: 99%
“…Nevertheless, palliative chemotherapy can improve overall survival compared with no treatment without impairing quality of life (Mallinson et al, 1980;Leonard et al, 1992;Palmer et al, 1994). Objective response rates remain low with most single-agent chemotherapy including 21 -26% with 5FU (Carter, 1975;Moertel, 1976), 26% with ifosfamide (Bernard et al, 1986), 22% with epirubicin (Wils et al, 1985) and 21% with cisplatin (Wils et al, 1993).…”
mentioning
confidence: 99%